Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Ulkus Diabetikum Di Ruang Interne Pria RSUP Dr. M. Djamil Padang - Sigit Irman; Kheniva Diah Anggita; Aulia Asman; Mike Asmaria (CV. ITTC INDONESIA, 2026)
Diabetic ulcers are one of the chronic complications of diabetes mellitus, characterized by the presence of wounds on the skin surface of individuals with diabetes mellitus. Diabetic ulcers occur due to disorders of the peripheral arterial blood vessels triggered by elevated blood glucose levels above normal values. The number of people with diabetes mellitus in Indonesia is estimated to reach 19.5 million adults, with the prevalence of diabetic ulcers ranging from 7% to 15%. Data from the Padang City Health Office in 2022 show that the number of diabetes mellitus patients ranges from 6,000 to 8,000, with the prevalence of diabetic ulcers around 10–20%. This study aims to provide medical-surgical nursing care for patients with diabetic ulcers at RSUP Dr. M. Djamil Padang. The subject of this case study is Mr. A, who was treated in the male internal medicine ward. The method used was direct observation to identify the patient’s problems. The nursing problems identified included acute pain, impaired skin or tissue integrity, unstable blood glucose levels, and ineffective peripheral perfusion. After five days of implementation, most of the nursing problems were resolved. Patients and their families are advised to maintain a healthy lifestyle, especially dietary patterns, to prevent worsening of the condition.